2010
DOI: 10.1103/physreva.81.033604
|View full text |Cite
|
Sign up to set email alerts
|

Spinor condensate ofRb87as a dipolar gas

Abstract: We consider a spinor condensate of 87 Rb atoms in the F = 1 hyperfine state confined in an optical dipole trap. Putting initially all atoms in the m F = 0 component, we find that the system evolves toward a state of thermal equilibrium with kinetic energy equally distributed among all magnetic components. We show that this process is dominated by the dipolar interaction of magnetic spins rather than spin-mixing contact potential. Our results show that because of a dynamical separation of magnetic components, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The dynamics of this quantum phase transition has been investigated in Refs. [5,[24][25][26][27][28]. When q < 0, the fully polarized state with m = 1 or −1 can minimize both the ferromagnetic interaction and the quadratic Zeeman energy.…”
Section: Ground-state Phase Diagram In the Absence Of Mddimentioning
confidence: 99%
“…The dynamics of this quantum phase transition has been investigated in Refs. [5,[24][25][26][27][28]. When q < 0, the fully polarized state with m = 1 or −1 can minimize both the ferromagnetic interaction and the quadratic Zeeman energy.…”
Section: Ground-state Phase Diagram In the Absence Of Mddimentioning
confidence: 99%
“…It is certainly less obvious that alkali atoms (whose magnetic dipole moment is an order of magnitude lower than that of chromium atoms) might be a good candidate to observe how spin is transmitted into orbital motion. However, some authors suggested that the magnetic dipolar interactions could already lead to observable effects in condensates of alkali atoms [9,[11][12][13][14][15][16][17]. Also a first experiment showed that a spin-1 87 Rb spinor condensate can exhibit dipolar properties [18].In this Letter we demonstrate that controlling the dipolar interactions by using an oscillating magnetic field is a perfect way to observe the Eintein-de Haas effect in alkali condensates provided it is done under a resonance condition.…”
mentioning
confidence: 99%
“…In the system composed of 52 Cr atoms [25][26][27][28] Feshbach resonances can enhance the effect of dipole-dipole forces. It was suggested in [29][30][31][32][33], and confirmed in [34], that dipolar effects may be observed also in the spinor F = 1 87 Rb BEC. The existence of long-range interactions is a motivating factor for studing systematically the effect of dipolar interactions on the level of squeezing in the simplest F = 1 spinor BECs.…”
Section: Introductionmentioning
confidence: 98%